Hálózatok az oktatásban - Bertalan, Péter (Acta Scientiarum Socialium, 2015)
Networks in Education Modern social sciences are based on abstraction and integrated knowledge. One of the most typical characteristics of the recent educational system conveys up-to-date practical knowledge. In the 21st century the principles and goals of education are intimately linked with the challenges of globalization and the revolution in information technologies. The key elements of educational policies in industrial countries are: modernizing educational systems, widening the range of learning opportunities for all sections of the public, teaching digital literacy as a basic skill, equal to reading and writing in importance. Teaching history has always been a basic question in education. Besides the serious professional debates there have always been public discussions on the issue of teaching this subject. The professsionals themselves in the stricter sense, the scholars of science and education could not even protect the rank and honour of the subject all the time. This is not considered to be a peculiar Hungarian phenomenon as for instance in England from the 1960’s the crisis of history teaching has arisen from time to time too and it was predicted that it would be deleted from the curriculum as an independent subject. In other cases narrowing the framework of the subject or teaching it in the scope of integrated social knowledge has been brought up. Developing the multi- and interdisciplinary way of thinking, formulating the abstractional skills and raising high school students’ time and space dimension cannot be avoided.
Keywords: modern social sciences; abstraction; knowledge; modern educational system